10-43=39+7(x-10)

Simple and best practice solution for 10-43=39+7(x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-43=39+7(x-10) equation:



10-43=39+7(x-10)
We move all terms to the left:
10-43-(39+7(x-10))=0
We add all the numbers together, and all the variables
-(39+7(x-10))-33=0
We calculate terms in parentheses: -(39+7(x-10)), so:
39+7(x-10)
determiningTheFunctionDomain 7(x-10)+39
We multiply parentheses
7x-70+39
We add all the numbers together, and all the variables
7x-31
Back to the equation:
-(7x-31)
We get rid of parentheses
-7x+31-33=0
We add all the numbers together, and all the variables
-7x-2=0
We move all terms containing x to the left, all other terms to the right
-7x=2
x=2/-7
x=-2/7

See similar equations:

| 5x+32=7x-12 | | |7x+5|+7=65 | | 2(3x-7)=10-8 | | 7(4+3p)+8=141 | | 3x-10+x+4+2x+4=180 | | 7x+5=72 | | 5x²+37x+54=0 | | 6/b=3/5 | | 5x²-37x+54=0 | | 5(5x+6)=25+30 | | 84=w6 | | (2a-2)=2(3a-3) | | 2s–12+2s=4s–12 | | 5-2x=8-4x | | 2x^2+8x-5=8 | | 0=n^2-19/3n+2 | | x2−3x−18=10 | | 5=3f+2 | | 18-(3x-5)=5(x-1)-6 | | 2w+2(3w-5)=82 | | 4=-7x+8x | | X/3-2x+1/2=5/6 | | (2x+1)^2-(-x+1)^2=(x-1)(3x+2) | | -7p+8p=7 | | 0.02(y-9)+0.18y=0.14y-0.03(10) | | 48-3x=-109-8x | | 3x-5=5x/x-3/x | | -6(v-1)=5v-49 | | -281=1-6(5-6x) | | 10x-21=4x | | 7x-4;x=5 | | 8/9(54-36)+2=-3/4(-40+16x)+90x |

Equations solver categories